Stimulus control, shaping of verbal behavior and correspondence in Shakespeare's "Othello". (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
Researchers have analyzed literature for its evident psychological content. However, behavioral interpretations of fictional plays are rare because, when behaviorists study works of literature, they often analyze the behavior of the author/artist or use it to illustrate behavioral phenomena. With fiction as a subject for analysis, one has to consider that the characters described in the piece ultimately behave under the same controls as do real people under natural conditions. Theater plays revolve, almost exclusively, around the verbal behavior of characters, and then it is relevant to analyze the controls on their speeches. Using characters from the play "Othello" by W. Shakespeare as subject, contingencies were verified to show functional relationships between verbal responses and control stimuli in the intraverbal chained behaviors of problem solving. Functional analyses of verbal responses were made through the identification of behavior instances and verification of antecedents and consequents relevant to the emission of specific responses.
Keywords: Verbal behavior; Lie; Functional analysis; Theater play; Shakespeare